LINGUISTIC VARIATION BETWEEN MALE AND FEMALE STUDENTS IN ACADEMIC WRITING - Asra, Surya; Wiradisastra, Grace Josephine Tiwon (Universitas Islam Sumatera Utara (UISU), 2022)
The variation of linguistic characteristics in academic writing between male and female is inevitable to happen. Therefore, this study aimed at finding out the differences of male and female students in linguistic characteristics of academic writing from perspective of linguistics, especially at the level of text analysis. The quantitative research method with convergent parallel design was used to analyze sixty students’ essay writing chosen by using a purposive sampling technique. The result revealed that there were some differences of linguistic characteristics in academic writing between male and female. The female students outperformed male students in all linguistic characteristics in text-level analysis. The female students were found more capable in paragraphing competences, linking devices, text output counts, topical organization, and ending. The findings generally support the notion that differences of linguistic characteristics between male and female should be considered in teaching academic writing to create a friendly teaching-learning process for both genders.